2013
DOI: 10.1111/j.1444-0938.2012.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary plasmacytoma of the eyelid: A case report and review of literature

Abstract: Primary extramedullary plasmacytomas of the eyelid are rare with only five other cases reported in the literature. A 43-year-old Chinese man presented with painless swelling of the left lower eyelid that developed over the past two years. An incisional biopsy and histopathological analysis of the lesion revealed a primary extramedullary plasmacytoma of the eyelid. The tumour was completely excised. There has been no tumour recurrence over the last five years. This tumour should be among those considered when e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The organs involved in the SPB are mainly axial skeletal bones, such as vertebra and skull, while in EMP, the head and neck, nasal cavity and nasopharyngeal are commonly involved 6 . It has been reported that the rate of relapse after treatment for extramedullary plasmacytoma is 6-10% 9 . Also, MM is characterized by the proliferation of abnormal plasma cells and is usually limited to bone marrow 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The organs involved in the SPB are mainly axial skeletal bones, such as vertebra and skull, while in EMP, the head and neck, nasal cavity and nasopharyngeal are commonly involved 6 . It has been reported that the rate of relapse after treatment for extramedullary plasmacytoma is 6-10% 9 . Also, MM is characterized by the proliferation of abnormal plasma cells and is usually limited to bone marrow 10 .…”
Section: Discussionmentioning
confidence: 99%
“…SEP is very rare and accounts only for about 3% of all PCN (4). Although SEP may occur throughout the body, the majority of cases occur in the head and neck region, particularly in the upper airways, including the nasal cavity, sinuses, oropharynx, salivary glands, and larynx, it also can be seen in gastrointestinal tract, pancreas, liver, parotid gland, respiratory system, central nervous system, thyroid, lymph nodes, mammary gland, testes, retroperitoneum or skin (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The diagnosis of SEP requires the presence of extramedullary tumor infiltrated with clonal plasma cells and bone marrow biopsy without any clonal plasma cell in the absence of any multiple myeloma symptoms (1,18).…”
Section: Discussionmentioning
confidence: 99%
“…According to 2017 WHO classification for plasma cell neoplasms (PCN), it includes non-IgM monoclonal gammopathy of undetermined significance (MGUS), plasma cell myeloma (PCM), plasmacytoma, monoclonal immunoglobulin deposition disease and PCN with associated paraneoplastic syndrome. Plasmacytoma is further subdivided into solitary plasmacytoma of bone (SPB) and extramedullary system (10), central nervous system (11), thyroid (12), lymph nodes (13), breast (14), testes (15), retroperitoneum (16), or skin (17) etc. Before being diagnosed, it is necessary to perform relevant examinations to ascertain whether there is Bence-Jonce protein in the blood and urine, osteolytic lesions in spine and pelvis, renal insufficiency and hypercalcemia, to completely rule out multiple myeloma (1,18).…”
Section: Introductionmentioning
confidence: 99%
“…The definitive diagnosis of plasmacytoma is by histopathological examination of the biopsy specimen. 12,13 On the basis of clinical evaluation, the common differential diagnoses include uveitis, inflammatory granuloma and uveal tumours. 7,8 Our patient presenting with signs of uveitis in a TB endemic region 14 and giving a positive contact history, chest imaging suggestive of past infection and initial response to topical steroids, the commoner diagnosis of tubercular iris granuloma was made.…”
Section: Discussionmentioning
confidence: 99%